Elastic Light Tunable Tissue Adhesive Dendrimers - Feng, Gao (2017)
Development of bioadhesive formulations for tissue fixation remains a challenge. The major drawbacks of available bioadhesives are low adhesion strength, toxic byproducts, and complexity of application onto affected tissues. In order to address these problems, this study has developed a hydrogel bioadhesive system based on poly amido amine (PAMAM) dendrimer, grafted (conjugated) with UV-sensitive, 4-[3-(trifluoromethyl)-3H-diazirin-3-yl] benzyl bromide (PAMAM-g-diazirine). This particular diazirine molecule can be grafted to the surface amine groups of PAMAM in a one-pot synthesis. Diazirine functionalities are carbene precursors that form covalent crosslinks with hydrated tissues after low-power UV activation without necessity of free-radical initiators. The rheological properties and adhesion strength to ex vivo tissues are highly controllable depending on diazirine grafting, hydrogel concentration, and UV dose intensity fitting variety types of tissues. Covalent bonds at the tissue/bioadhesive interface provide robust adhesive and mechanical strength in a highly hydrated environment. The free flowing hydrogel conversion to elastic adhesive after UV activation allows intimate contact with the ex vivo swine tissue surfaces with low in vitro cytotoxicity observed, making it a promising bioadhesive formulation toward clinical applications.